Empowerment of School Adolescents for Prevention of Gender Discrimination and Sexual Harassment: Application of an Integrated Experiential Learning Package - Thapa, Rita; Subedi, Raj Kumar; Pun, Bindu; Chand, Sunita Kumari; Thakur, Dip Narayan; Thapaliya, Radhika; Karki, Sarita; Regmi, Gorakh; Pandey, Vikrant (Journal of Nepal Health Research Council, 2025)
Background: The prevalence of gender discrimination and sexual harassment/ violence among children is alarmingly high in Nepal. This study aimed to measure aggregate changes in knowledge, attitude, and skills among school adolescents on gender discrimination; sexual harassment, mindfulness of breathing; and self-defense skills, with application of an integrative experiential learning modules. Methods: A quasi-experimental study was carried out among 3661 students from 8-9 grades (1880 intervention and 1781 control) in 52 community schools across the seven provinces. Pre- and post-intervention self-reported surveys were conducted among the intervention and control groups before and after intervention of 24 learning hours. We used a mixed two-way effects model to measure the changes in composite indices between pretest and posttest among both the groups. Results: We found statistically significant increment (P<0.0001) in knowledge, attitude and skills on gender norms, gender discrimination, sexual harassment, self-defense, reporting sexual harassment, legal measures and mindfulness of breathing technique among the intervention group compared to that in the control group. Conclusions: These findings, though measured immediately after the intervention, offer initial evidence that school adolescents could be empowered to prevent the risks of gender discrimination and sexual harassment. Keywords: Empowerment; gender discrimination; school-based intervention; sexual harassment; self-defense.